Introduction to electronic defense systems - Neri, Filippo (Artech House electronic warfare library., 2018)
Over the past decade, new cutting-edge technologies have drastically changed the way radar and electronic warfare systems are implemented. This extensively revised and expanded edition of an Artech House bestseller delivers the most up-to-date overview of electronic defense systems. Bringing practitioners up-to-speed with the latest technological advances, the Third Edition details a completely new method of implementing these modern systems. Moreover, this edition is packed with updated illustrations of key assets, including aircraft, ships, and radars.nnReaders get a solid understanding of how sophisticated electronic warfare weapon systems work, and how these weapons can be intercepted and electronically jammed. From search and tracking radar, IR systems, and communication systems ... to electronic intercept systems, countermeasures, and counter-countermeasures, the book explores a broad spectrum of defense equipment. It explains how these systems operate, the advantages and drawbacks of each system, and the theories on which these systems are based. This authoritative resource includes 180 illustrations and 400 equations that support key topics throughout the book.